Review of Congestion Control Methods in Named Data Network - Zhang, Bohan (International Journal of Computer Science and Information Technology, 2024)
In recent years, with the development of new networking technologies, the demand for networks has shifted from simple resource sharing to large-scale content distribution. This change has led to the gradual inadequacy of the traditional TCP/IP architecture in meeting the current needs of production and daily life. In this context, Named Data Networking (NDN) has emerged. NDN networks, with their content-centric nature and features such as in-network caching, multi-source forwarding, and routing control, have attracted significant attention from researchers both domestically and internationally. However, the novel architecture of the network also presents new challenges for congestion control research in NDN. This paper conducts thorough research on the related work of congestion control in NDN, provides a detailed overview of existing research efforts in NDN congestion control, and describes potential future research directions in NDN congestion control. The aim is to provide valuable references for future research on congestion control in NDN.